Chapter Spatial planning prospects on changeability process of urban and natural (Land)scape relations - The dynamics of Ancona on the West and Rijeka on the East Adriatic Coast - Sopina, Ana (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The urban and natural landscape relations are temporal, spatial, and perceptive phenomena complemented by providing functions and holistic principles that arise from the spatial planning approach. The research aims to investigate how spatial planning guides the changeability process of landscape relations in the Adriatic cities of Ancona and Rijeka settled between two strong natural elements of the sea and the mountains. The research interconnects the Heritage Urbanism approach and the Urbanscape Emanation concept in establishing identity factors, evaluation criteria, and enhancement models.